Case Study on Somatic Symptoms in AdolescentsThe Pain Puzzle - Mahadevan, Anuradha; Dr. T. Veeramani, (Journal of Advanced Research in Psychology & Psychotherapy (E-ISSN: 2581-5822), 2022)
Somatic symptoms in adolescents can lead to debilitating impact on their academic and social functioning. It could be a manifestation of anxiety and way of responding to a situation which is perceived as a threat. Unnecessary invasive medical interventions cause more agony to the adolescent. Somatic symptoms in adolescents are one area of research and most misdiagnosed with more common mental disorders with similar symptoms. Early recognition of such disorders can save years of pain, suffering, and cost. Clinical evaluation revealed that the majority of adolescents manifested extremely variable school performance, disruptive behavior, trance, mood swings, and depression. Recent research is identifying a number of factors linking to this and its hidden behind. This paper aims to have a better understanding of somatic symptoms in adolescents and its impact on their academic, personal, social functioning. Discussions are made regarding management plans, and therapeutic techniques that have helped these adolescents to attain their functionality and helping them cope with the same.